DC fault ride through operation of a full-bridge MMC converter - Feng, Yixue (2016)
In recent years the growth of renewable energy has encouraged the development of HVDC grids. One challenge of building HVDC grids is the power converter response to DC side faults. The full-bridge Modular Multilevel Converter (MMC) is a desired power converter topology which is used in HVDC grids due to its scalability, modularity and capability of blocking DC side faults.